A Morphological Study of Alumina Hollow Fiber Membrane - Asrar Al-Obaidy (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Morphologies of ceramic hollow fiber membranes prepared by a combined phase-inversion and sintering method were studied. The organic binder spinning solution containing suspended Al₂O₃ powders was spun to a hollow fiber precursor, which was then sintered at elevated temperatures( 300 ˚C, 1400 ˚C, 25 ˚C) in order to obtain the Al₂O₃ hollow fiber membranes. The spinning solution consisted of polyether sulfone (PES), N-methyl-2-pyrrolidone (NMP), which were used as polymer binder, solvent, respectively. The prepared Al₂O₃ hollow fiber membranes were characterized by a scanning electron microscope (SEM). It is believed that finger-like void formation in asymmetric ceramic membranes is initiated by hydrodynamically unstable viscous fingering developed when a less viscous fluid (non-solvent) is in contact with a higher viscosity fluid (ceramic suspension containing invertible polymer binder). The effects of the air-gap (0 cm, 2 cm, 15 cm) on fibre morphology have been studied and it has been determined that viscosity due to change in air-gap is the dominating factor for ceramic systems.